2003
DOI: 10.2166/ws.2003.0101
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive flushing for discolouration event mitigation in water distribution networks

Abstract: Discolouration is one of the biggest causes of customer complaint associated with potable water. The flushing of systems has been widely identified as an appropriate pro-active means of removing material from distribution networks and hence controlling discolouration. Such flushing involves creating aggressive hydraulic forces within the network such that the materials that contribute to discolouration are mobilised and removed. Understanding of the causes and mechanisms leading to discolouration are poor. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…This indicates that particulate turbidity is typically the cause of discolouration as reported by customers, Vreeburg and Boxall (2007). Flushing trials also report iron and manganese as dominant within discoloured water samples with a strong correlation between their concentration and the turbidity of the water, Gauthier et al (2001), Mc Coy andOlsen (1986) and Boxall et al (2003).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This indicates that particulate turbidity is typically the cause of discolouration as reported by customers, Vreeburg and Boxall (2007). Flushing trials also report iron and manganese as dominant within discoloured water samples with a strong correlation between their concentration and the turbidity of the water, Gauthier et al (2001), Mc Coy andOlsen (1986) and Boxall et al (2003).…”
Section: Introductionmentioning
confidence: 85%
“…Discolouration as reported by customers is either caused by the presence of fine particles in the water, measured as turbidity, or by true colour (Gauthier et al 1996;Marshall 2001;Polychronopolous et al 2003;Ryan et al 2003). However, flushing experiments carried out by Boxall et al (2003), Polychronopolous et al (2003), Prince et al (2003) and Seth et al (2003) found very little true colour, but significant turbidity. This indicates that particulate turbidity is typically the cause of discolouration as reported by customers, Vreeburg and Boxall (2007).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reasoning behind this is partly the theoretical approach based on Shields' and Stokes' equations, though this leads to lower velocities than 1.5 m/s for example (Boxall et al 2003). For the other part, the value of 1.5 m/s is based on practical experience that these velocities are significantly above the normal daily maximum velocities.…”
Section: Minimum Velocitymentioning
confidence: 99%
“…However, recent studies have shown that other sources of particulate matter, aside from corrosion, can play a role in water discoloration [4][5][6][7]. Additionally, it has been reported that the accumulation of particulate matter is related to biological activity, and 1% to 12% of the organic matter may consist of bacterial biomass, thus making deposits an important factor to consider when evaluating the hygienic safety of drinking water [4].…”
Section: Introductionmentioning
confidence: 99%